Fatal Transorbital Intracranial Penetrating Injury Due to a Bicycle Brake Handle. (September 2018) - Sathish, K; Chaudhari, Vinod Ashok; Murthy, Abilash Srinivasa
Abstract : Abstract: Transorbital intracranial injuries are uncommon and mostly accidental in nature. These injuries are usually associated with high mortality. The key to preventing this mortality involves an early diagnosis of intracranial injuries and immediate and appropriate management. Any delay can pose a serious risk to the patient's life. A case of a 55-year-old man who had experienced an accidental self-fall while riding a bicycle is presented. Initially, he was treated at a primary health center. He was referred to the tertiary care institute due to unavailability of ancillary investigation at the primary health center. He was declared dead on arrival at the casualty in the tertiary institute. On autopsy, it was observed that the injury above the right side of the upper eyelid was penetrating the right side roof of the orbit and the right cerebral cortex and brainstem. The highlighting feature of the case is that, despite the fatal penetrating brain injury, the eyeball did not sustain any major injury.